Comparative Analysis of Various Fingerprint Image Enhancement Algorithms (International Journal of Engineering and Computer Science, 2017)
There are various biometric features for personal identification but Fingerprints are today the most widely used biometric features for the same.  Many automatic systems are there for fingerprint enhancement which is based on ridges and valleys. Automatic fingerprint recognition system is totally based on Fingerprint enhancement. It is necessary to choose the suitable enhancement technique for fingerprint, in order to reduce the post-processing part of the fingerprint recognition system. Different Fingerprint Enhancement techniques have been discussed in this work. These different methods are used by which the image quality is enhanced and Fingerprint Matching techniques are applied. These algorithms contribute to recognize the person and provide authenticity on the basis of physiological or behavioral characteristic possessed by the user. But, author’s focus is on the methods of enhancement. By having the proper analysis of all the existing methods and algorithms, author can review the literature of fingerprint image enhancement methods, so as to design a new advanced and modified method for the same. With the help of these techniques we can prepare a system which is helpful to enhance the watermarked fingerprints.